Fractal Cityscape - Li, Baihua; Miller, James (International Journal of Virtual Reality, 2010)
There is an increasing demand for the simulation of large-scale "free-flow" urban environments in games or other virtual reality worlds. Currently most 3D cityscapes are generated by time consuming manually pre-scripted "room-to-room" approaches. Although the effectiveness of fractal modelling of rural landscape or architecture has been studied extensively, there is a relative dearth of research on fractal modelling of cityscapes. Inspired by modern fractal city theory, we intend to develop an automatic fractal-based method to address this problem. In particular, we will investigate how fractal theory can be used to mathematically simulate the multi-level hierarchical urban structure corresponding to various land use property probabilities of city regions. Tentative findings and results are presented in this paper